Przemoc wobec dzieci w rodzinie - Helios, Joanna; Jedlecka, Wioletta (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2019)
Violence against children is the subject of interdisciplinary scientific research. Most often, this issue is considered on the basis of pedagogical and psychological sciences, less often on the ground of law sciences. Considerations focused on four main forms of violence against children in the family: physical and psychological violence, sexual violence and neglect. The monograph presents many aspects of physical abuse of a minor, starting with the so-called innocent spanking, by jerking, beating, mutilation, and ending with depriving a child of life. The considerations have a broad social, psychological, philosophical and even medical context. The effects of physical violence experienced in childhood, reflecting on human life and health in an unconscious way - syndrome of a lacerated infant, as well as conscious - post-traumatic stress disorder or abused child syndrome are shown. A detailed analysis of legal solutions relating to physical abuse of children has been made. The paper also presents a broad spectrum of forms of psychological violence with numerous references to research conducted in the area of social sciences and pointed to the psychological, physical and somatic consequences of experiencing wrongs. For the considerations, the legal thread is important, in which normative solutions from various branches of law were analysed. An important part of the book is a section devoted to sexual violence against children, which belongs to the most hidden problems in the family. It is also the most harmful and socially stigmatized form of child abuse. It has been treated fairly widely due to the specificity and the fact that some of its varieties may extend beyond the family. The neglect of the child is a complement to the three main forms of violence. The analyses of "neglect" were made from various perspectives, ranging from providing help to parents who are not educated, by limiting and depriving them of power over a child, and ending with administering sanctions provided for by criminal law.
Keywords: eurosieroctwo; physical violence; child rearing; psychological violence; sexual violence; incest; pedophilia; neglect; euro- orphans